Mass fux decay timescales of volcanic particles due to aeolian processes in the Argentinian Patagonia steppe - Dominguez, Lucia; Rossi, Eduardo; Mingari, Leonardo; Bonadonna, Costanza; Forte, Pablo Brian; Panebianco, Juan Esteban; Bran, Donaldo Eduardo (Springer Nature, 2023)
We investigate the timescales of the horizontal mass flux decay of wind remobilised volcanic particles in Argentina, associated with the tephra-fallout deposit produced by the 2011–2012 Cordón Caulle (Chile) eruption. Particle removal processes are controlled by complex interactions of meteorological conditions, surface properties and particle depletion with time. We find that ash remobilisation follows a two-phase exponential decay with specific timescales for the initial input of fresh ash (1–74 days) and the following soil stabilisation processes (3–52 months). The characteristic timescales as a function of particle size shows two minimum values, identified for sizes around 2 and 19–37 μ m, suggesting that these size-range particles are remobilised more easily, due to the interaction between saltation and suspension-induced processes. We find that in volcanic regions, characterised by a sudden release and a subsequent depletion of particles, the availability of wind-erodible particles plays a major role due to compaction and removal of fine particles. We propose, therefore, a simple and reproducible empirical model to describe the mass flux decay of remobilised ash in a supply-limited environment. This methodology represents an innovative approach to link field measurements of multi-sized and supply-limited deposits with saltation erosion theory.